Down the Yukon - Hobbs, Will. (New York : HarperCollins, 2001)
In the wake of Dawson City$1 (Bs Great Fire of 1899, sixteen-year-old Jason and his girlfriend Jamie canoe the Yukon River across Alaska in an epic race from Canada$1 (Bs Klondike to the new gold fields at Cape Nome.s
Sequel to: Jason$1 (Bs gold.s
Keywords: Racing -- Fiction; Contests -- Fiction; Voyages and travels -- Fiction; Nome Region (Alaska) -- Gold discoveries -- Juvenile fiction; Nome Region (Alaska) -- Gold discoveries -- Fiction; Yukon River (Yukon and Alaska) -- Fiction